Widening Access for Education: Proposing a Conceptual Model for Integrated Open and Distance Learning (ODL) on Demand - Norbaini Abdul Halim; Nur Azlin Omar; Lim , Tick Meng; Siew , Nooi Phang; Chooi , Chea Chiam (2009)
The education world has seen a dramatic change in the mode of learning and teaching. Attention has been drawn to open and distance learning (ODL) as one method of educational instruction using advanced information and communication technology (ICT) as the enabler. ODL has become the means by which education can be accessed by all who so require, anywhere, anytime. Thus, ODL itself must be able to meet the “demands” of its stakeholders including learners and facilitators. There has to be in place a system that can support instant delivery of learning and guiding materials to learners and enables facilitators to guide and assess their learners both synchronously and asynchronously. Such a system should be holistic and dynamic in a way that it can cater ‘on demand’ any requests from the stakeholders. This paper proposes a conceptual model for integrated ODL on demand which can be utilised for the teaching and learning of a range of courses. The proposed model’s delivery mode would be based upon learning through visualisation, interaction, collaboration, exploration and a host of possible alternatives that can be replicated for any course carried out by ODL institutions including Open University Malaysia (OUM). (Authors' abstract)